Refugees welcome? : difference and diversity in a changing Germany - Bock, Jan-Jonathan HerausgeberIn; Macdonald, Sharon Jeannette 1961- HerausgeberIn (Berghahn, 2019)
Making Germans and non-Germans -- Language as battleground : "speaking" the nation, lingual citizenship and diversity management in postunification Germany / Uli Linke -- Diversity and unity : political and conceptual answers to experiences of differences and diversities in Germany / Friedrich Heckmann -- Jews, muslims and the ritual male circumcision debate : religious diversity and social inclusion in Germany / Gokce Yurdakul -- Potential for change -- Islam, vernacular culture and creativity in Stuttgart / Petra Kuppinger -- "Neukolln is where I live; it's now there I'm from" : children of migrants navigating belonging in a rapidly changing urban space in Berlin / Carola Tize and Ria Reis -- The post-migrant paradigm / Naika Foroutan -- Refugee encounters -- New year's eve, sexual violence and moral panics : ruptures and continuities in Germany's integration regime / Kira Kosnick -- Solidarity with refugees: negotiations of proximity and memory / Serhat Karakayali -- Negotiating cultural difference in Dresden's Pegida movement and Berlin's refugee church / Jan-Jonathan Bock -- New initiatives and directions -- Interstitial agents : negotiating migration and diversity in theatre / Jonas Tinius -- Articulating a noncitizen politics : nation-state pity versus democratic inclusion / Damani J. Partridge -- The refugees-welcome movement : a new form of political action / Werner Schiffauer -- Concluding reflection: refugee futures and the politics of belonging / Sharon Macdonald -- Index